Wealth transfers and labour supply: impact of inheritances and gifts by gender in Europe. Issue 8 (3rd June 2021) - Malo, Miguel Á.; Sciulli, Dario
Abstract : Purpose: The authors analyse how the receipt of a wealth transfer (inheritance or gift) affects labour force participation in 14 EU countries. They compare the effect of receiving an inheritance or a gift and investigate different behaviours at the gender level and educational level and for elderly individuals. Design/methodology/approach: The authors use data from the Household Finance and Consumption Survey for 14 European countries and adopt an instrumental variable approach. They use information on the type of donor (family and nonfamily) to infer the degree of anticipation of a wealth transfer. Findings: The authors find that unexpected wealth transfers have a negative impact on labour force participation, with a stronger impact for gifts than for inheritances. For gender, they find larger negative impacts for females than for males, which is in line with a weaker attachment to the labour market. Receiving an unexpected wealth transfer may also result in early retirement. Originality/value: The paper offers a novel comparison of the effect of receiving an inheritance or a gift on labour force participation using a unique European dataset. The authors investigate whether males and females react differently to the receipt of a wealth transfer and the existence of different responses at the educational level and for elderly individuals.